Alterações funcionais e estruturais do coração produzidas pelo Sacubitril-Valsartana na cardiotoxicidade induzida pela doxorrubicina em ratos - Cabral, Eduardo de Sales (2021)
Introduction: The necessary and desired changes in the heart resulting from the toxicity induced by doxorubicin have been investigated in our laboratory using experimental models with Wistar rats. The combination of a neprilysin inhibitor and an angiotensin II AT1 receptor blocker (ANRI) reduces heart failure mortality rates, but there are few studies of its effects on cardiotoxicity due to doxorubicin. Objective: To characterize the functional and structural alterations of the heart produced by sacubitril-valsartan in doxorubicin-induced cardiotoxicity. Material and methods: 35 male Wistar rats were used, with an average initial weight of 287 grams, randomly divided into five groups: Control (C-5), Doxorubicin (DX-8), Sacubitril-Valsartan (ARNI=5), Doxorubicin/ Valsartan (DXVAL-7) and Doxorubicin/Sacubitril-Valsartan (DXARNI-10). The experiment lasted eight weeks. Doxorubicin was administered in an aqueous solution injected into the corresponding groups via intraperitoneal, three times/week, over two weeks, reaching a cumulative dose of 7.5 mg/kg of animal weight. Two weeks after the end of exposure to the chemotherapeutic drug, the administration of sacubitril-valsartan, at a dose of 100 mg/kg, was started, once a day, for two weeks. Body weight at the beginning and at the end of the experiment was recorded; the total heart weight was obtained at the end of the protocol; the indexed heart mass was calculated from the ratio between heart weight and body weight. Left ventricular function, systolic and diastolic diameters, and the thickness of the interventricular septum and the posterior wall of the left ventricle were obtained by echocardiography at the end of the experiment. Results: The final body weight, the change in body weight (initial x final) and heart weight were lower in the ARNI, DX, DXVAL and DXARNI groups, when compared to the C group. The indexed heart mass showed no statistically significant change. The thickness of the interventricular septum in diastole (SIVd) was greater (p=0.04) in DX, compared to the ARNI. Compared to C, the DIVEd was lower (p=0.03) in DX, and lower with a strong tendency (p=0.06) in the DIVEs, the VFVEd was lower (p=0.02) in DX and DXARNI. Systolic VFVE was lower (p=0.04) in DX. Conclusion: The study confirms the hypothesis that sacubitril-valsartan is useful, improving diastolic and structural functional parameters of the heart altered after experimental exposure to doxorubicin, also suggesting its participation in LV reverse remodeling. The results also confirm that, in the present study, the cardiotoxic effects of doxorubicin consist of predominantly diastolic alterations and point towards the use of the model in future studies related to pathophysiology and pharmacological tests in ICFEp.